Aortic valve cell seeding into decellularized animal pericardium by perfusion‐assisted bioreactor. (15th May 2018) - Amadeo, Francesco; Boschetti, Federica; Polvani, Gianluca; Banfi, Cristina; Pesce, Maurizio; Santoro, Rosaria
Abstract: Animal‐derived pericardium is the elective tissue employed in manufacturing heart valve prostheses. The preparation of this tissue for biological valve production consists of fixation with aldehydes, which reduces, but not eliminates, the xenoantigens and the donor cellular material. As a consequence, especially in patients below 65–70 years of age, the employment of valve substitutes contaning pericardium is not indicated due to progressive calcification that causes tissue degeneration and recurrence of valve insufficiency. Decellularization with ionic or nonionic detergents has been proposed as an alternative procedure to prepare aldehyde‐ or xenoantigen‐free pericardium for biological valve manufacturing. In the present contribution, we optimized a decellularization procedure that is permissive for seeding and culturing valve competent cells able to colonize and reconstitute a valve‐like tissue. A high‐efficiency cellularization was achieved by forcing cell penetration inside the pericardium matrix using a perfusion bioreactor. Because the decellularization procedure was found not to alter the collagen composition of the pericardial matrix and cells seeded in the tissue constructs consistently grew and acquired the phenotype of "quiescent" valve interstitial cells, our investigation sets a novel standard in pericardium application for tissue engineering of "living" valve implants.